The comparison of pollen abundance in air and honey samples - Ingrida Šaulienė; Laura Šukienė; Auste Noreikaite-Merkeliene; Vidmantas Pileckas (Acta Agrobotanica, 2015)
Honey as a food has long been used in human nutrition and is still popular. Honey is important because of its therapeutic, prophylactic and strengthening value. Pollen is one of the most decisive components that ensure the quality and type of honey. Modern society becomes more and more sensitive to airborne pollen. Therefore, it is crucial to determine the composition of allergenic plant pollen in natural honey. For this purpose, we studied and compared pollen abundance in honey and air samples collected in Lithuania. Standard methods for pollen investigation in air and honey were used in this study. The botanical diversity of pollen identified in honey and air samples indicates 10 morphotypes: 8 of woody plants and 2 of herbaceous plants, in both the honey and air samples. Salix pollen counts in the honey were found to be highest among airborne pollen from May to September. The anemophilous allergenic pollen constituted 44 % of the total pollen detected in the honey.